Kralj mučenik in sproščena opatinja - Divjak, Alenka (Primerjalna književnost, 2020)
This article juxtaposes the activities of two saints, brother and sister, St Oswald (634-642) and St Aebbe (ca. 615-683), members of the royal family of Northumbria, and discusses their rather unconventional paths to sanctity. Oswald's efficiency and competent kingship were instrumental in reconverting Northumbria to Christianity, laying thus the foundations for the intellectual and spiritual growth of Christianity in Northumbria. Nevertheless, the Church of Northumbria was initially reluctant to raise Oswald to sanctity, and this reluctance ran against the wishes of Oswald's family and the majority of the population. Aebbe, on the other hand, was fully absorbed in the monastic sphere as an abbess and foundress of the monastic community at Coldingham (today's southern Scotland). However, if Oswald's achievements were fully recognized soon after his demise, Abbe's leadership of her monastic community seems to have been controversial. Oswald's cult began to be promoted soon after his death, Aebbe, by contrast, was never regarded as a saint in the Anglo-Saxon period. Her cult began to emerge only in the twelfth century when the recently established monastery in Coldingham needed a saintly predecessor and unlike her brother's cult, it never held an international appeal. Nevertheless, she was a respected local saint, notable for her numer-ous curative miracles, and her rise from oblivion remains a telling example of ecclesiastical spin in the field of the veneration of saints.
Keywords: 7.st.; cerkvena zgodovina; krščanstvo; Northumbrija; redovništvo; sv. Aebbe iz Coldinghama; sv. Oswald iz Northumbrije; svetniki